Thermophysical properties of aqueous N-methyldiethanolamine (MDEA) and ionic liquids 1-butyl-3-methylimidazolium trifluoromethanesulfonate bmimOTf, 1-butyl-3-methylimidazolium acetate bmimAc hybrid solvents for CO2 capture - Khan, S.N. (Institution of Chemical Engineers, 2017)
In this research work, thermophysical properties such as density, refractive index, surface tension, and viscosity of aqueous N-methyldiethanolamine (MDEA) and 1-butyl-3-methylimmidazolium trifluoromethanesulfonate bmimOTf, 1-butyl-3-methylimmidazolium acetate bmimAc hybrid solvents were investigated. All thermophysical properties were investigated at an atmospheric pressure, between the temperature ranges of 298.15 to 343.15 K with an interval of 5 K. In all samples, the concentration of MDEA was kept constant at 30 wt%, while the concentration of the ionic liquids was varied between 5–20 wt%. Experimental investigation demonstrated that the thermophysical properties were mainly dependent on the temperature and the concentration of the ionic liquids. All thermophysical properties were decreased with increase in temperature of the system. An increasing trend was observed in density, refractive index, and viscosity data with the increase in the concentration of the ionic liquids. The surface tension data for all samples under investigated was found to be in decreasing order with the increase in the concentration of the ionic liquids. It was also noticed that the use of two different ionic liquids has a different impact on the thermophysical properties of the hybrid solvents. Empirical correlations were used to correlate the experimental data of all the properties as a function of temperature and concentration of both the components (IL and amine). The correlated data were found to be in good agreement with the experimental data at all concentrations. © 2017 Institution of Chemical Engineers